Nanomaterials for diabetic wound healing: Visualization and bibliometric analysis from 2011 to 2021 - Zhang, Jun; Liu, Hongyan; Che, Tingting; Zheng, Yin; Nan, Xixi; Wu, Zhongming (Frontiers in Endocrinology, 2023)
Background: Nanomaterials have recently been shown to have a considerable advantage in promoting wound healing in diabetic patients or animal models. However, no bibliometric analysis has been conducted to evaluate global scientific production. Herein, this study aimed to summarize the current characteristics, explore research trends, and clarify the direction of nanomaterials and diabetic wound healing in the future. Methods: Relevant publications from 2011 to 2021 were collected from the Web of Science Core Collection on October 3, 2022. VOSviewer, CiteSpace, bibliometrix-R package, Origin 2021, and Microsoft Excel 2019 were used for bibliometric and visualization analyses. Results: We identified 409 publications relating to nanomaterials and diabetic wound healing. The number of annual productions remarkably increased from 2011 to 2021, with China and Shanghai Jiao Tong University being the most productive. The most prolific authors were Xu He and Hasan Anwarul, who had a larger number of citations and a higher H-index. The leading journal was the International Journal of Biological Macromolecules, with 22 publications. The most popular keywords were “nanoparticles,” “delivery,” “in vitro,” “electrospinning,” “angiogenesis,” and “antibacterial.” Keyword burst analysis showed “cerium oxide,” “matrix metalloproteinase 9,” “composite nanofiber,” “hif 1 alpha,” and “oxide nanoparticle” were emerging research hotspots. Conclusion: Our study is the first bibliometric analysis that comprehensively summarizes recent research status and hotspots. This provides evidence for researchers to further clarify the potential perspectives of research frontiers.